FAKTOR RISIKO KELUHAN CARPAL TUNNEL SYNDROME (CTS)PADA PEKERJA BAGIAN PACKING PERUSAHAAN PRODUKSIKAWAT LAS DI KOTA TANGERANG TAHUN 2022 - Dea Yolanda Mawaddah (2022)
Carpal Tunnel Syndrome (CTS) is a musculoskeletal disorder of the hands with symptoms of tingling, pain and numbness. CTS can cause an inability to grip. Packing workers have a high risk of CTS. The purpose of this study was to determine the risk factors for CTS complaints among packing workers at welding electrode manufacturer company in Tangerang in 2022. A cross sectional design was chosen for this research. The sample of this research consisted of 70 packing workers which were obtained from the minimum sample of Slovin calculation. Data were analyzed using a chi-square test. The results showed that there are 84,3% of packing workers had CTS complaints. The individuals factors which consist of age (p=0,042, POR=4,8; 95% CI=1,155-20,162) had a relationship with CTS complaints, meanwhile there were no relationship between gender (p=1,00, POR=0,8; 95% CI=0,211-2,392) and BMI (p=0,267, POR=4,390 95% CI=0,522-36,907) with CTS complaints. The occupational factors, such as years of service (p=0,038, POR=6,1; 95% CI=1,21 -30,828) and work posture (p=0,027, POR=4,7; 95% CI=1,224-18,049) had a relationship with CTS complaints. Therefore, workers are advised to stretch their hands before starting work to prevent muscle spasms.